Brain Tumors 2022
DOI: 10.5772/intechopen.100432
|View full text |Cite
|
Sign up to set email alerts
|

High Grade Meningiomas: Current Therapy Based on Tumor Biology

Abstract: Atypical (WHO grade II) and malignant meningiomas (WHO Grade III) are a rare subset of primary intracranial tumors. Due to the high recurrence rate after surgical resection and radiotherapy, there has been a recent interest in exploring other systemic treatment options for these refractory tumors. Recent advances in molecular sequencing of tumors have elucidated new pathways and drug targets currently being studied. This article provides a thorough overview of novel investigational therapeutics, including targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 175 publications
(223 reference statements)
0
14
0
Order By: Relevance
“…Loss of chromosome 22 [18] More frequently (87%) Less frequently (58%) are malignant, making up the bulk of meningiomas (WHO grade III) [8,10]. After age 65, the chance of high grade meningiomas dramatically increases with age.…”
Section: Grade-i Grade-ii and Grade-iiimentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of chromosome 22 [18] More frequently (87%) Less frequently (58%) are malignant, making up the bulk of meningiomas (WHO grade III) [8,10]. After age 65, the chance of high grade meningiomas dramatically increases with age.…”
Section: Grade-i Grade-ii and Grade-iiimentioning
confidence: 99%
“…It is thought that individuals with the genetic condition Neurofibromatosis type 2 (NF2) have an increased chance of developing meningioma. Additionally, meningiomas that are malignant or numerous may be more common in NF2 patients [10]. While postmenopausal women without these traits are more likely to have Grade I meningiomas, meningioma patients with past CVA and those with grade 4/4 vascularity are more likely to develop WHO Grade II-III tumors [11] (Table 1).…”
Section: Grade-i Grade-ii and Grade-iiimentioning
confidence: 99%
“…Eccentric nuclei, open chromatin, macronucleoli, and eosinophilic perinuclear inclusions, which might be whorled fibrils or compact, waxy spheres 32,33 …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that is why the EGFR inhibitors called erlotinib and gefitinib did not have significant survival at phase II studies in meningioma 79 . The 12‐month follow‐up demonstrated that for benign tumors, the 12‐month survival rate without any progression was 13%, and the 12‐month rate of overall survival was 50% 33 . The 6‐month survival rate for atypical meningioma and malignant meningioma tumors was 29%; the 12‐month survival rate was only 18%; and the 6‐month rate of overall survival was 71%; however, the 12‐month rate of overall survival was 65% 79 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation